2013
DOI: 10.4028/www.scientific.net/amr.716.413
|View full text |Cite
|
Sign up to set email alerts
|

Novel Profile Control Treatment Using Pore-Scale Polymer Elastic Microspheres

Abstract: In order to solve the deep profile control problem and improve oil recovery of the oilfield, a novel profile control agent pore-scale polymer elastic microspheres (PSPEMs) was synthesized. The swelling property of PSPEMs in aqueous solution was analyzed. Core flow test and double-tube sand pack models were used for studying profile control and flooding performance of PSPEMs in oil formation. The results show that PSPEMs have good swelling property in aqueous solution with high salinity, high temperature and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The pressure changing was detected by the sensor. The permeability ( k wb , given in units of μm 2 ) and the plugging rate (η, expressed in units of %) of the sand pack model after the plugging process were calculated using the following equations: , where Δ P is the injection pressure difference (given in units of 10 –1 MPa), Q is the injection rate (given in units of mL/s), μ is the viscosity of brine water (given in units of mPa s), A and L are the sectional area and length of the sand pack model, respectively (expressed in units of cm 2 and cm, respectively), and k wa is the initial permeability of the sand pack model (given in units of μm 2 ). The main equipment is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure changing was detected by the sensor. The permeability ( k wb , given in units of μm 2 ) and the plugging rate (η, expressed in units of %) of the sand pack model after the plugging process were calculated using the following equations: , where Δ P is the injection pressure difference (given in units of 10 –1 MPa), Q is the injection rate (given in units of mL/s), μ is the viscosity of brine water (given in units of mPa s), A and L are the sectional area and length of the sand pack model, respectively (expressed in units of cm 2 and cm, respectively), and k wa is the initial permeability of the sand pack model (given in units of μm 2 ). The main equipment is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…The pressure changing was detected by the sensor. The permeability (k wb , given in units of μm 2 ) and the plugging rate (η, expressed in units of %) of the sand pack model after the plugging process were calculated using the following equations: 38,39…”
Section: Methodsmentioning
confidence: 99%
“…The differential pressures (DP, given in units of MPa) were measured during the whole injection process. The permeability of the sand pack in the displacement process (k, given in units of lm 2 ), and the plugging rate (g, expressed in units of %) were calculated using the following equations (Qin and Li 2006;Lei 2011…”
Section: Core Flow Experimentsmentioning
confidence: 99%
“…Many chemical agents have been applied to control profile and enhance oil recovery of heterogeneous reservoirs. There are many cases reported that bulk gel, weak gel, colloidal dispersion gel (CDG), and precross-linked particle gel (PPG) can control profile and enhance oil recovery of heterogeneous reservoirs effectively and are widely used in oilfield development. In the early 21st century, a smart profile control and oil displacement agent with elasticity called “micron-size polyacrylamide microspheres (MPEMs)” was developed to control profile in oil reservoirs with high temperature and high salinity . The MPEMs are size- and strength-controlled, environmentally friendly, and not sensitive to reservoir minerals and formation water salinity.…”
Section: Introductionmentioning
confidence: 99%
“…5−15 In the early 21st century, a smart profile control and oil displacement agent with elasticity called "micron-size polyacrylamide microspheres (MPEMs)" was developed to control profile in oil reservoirs with high temperature and high salinity. 16 The MPEMs are size-and strength-controlled, environmentally friendly, and not sensitive to reservoir minerals and formation water salinity. They can deform depending on their elasticity and pass through the pore-throats under a large pressure difference to achieve a dynamic process of profile control and oil displacement.…”
Section: Introductionmentioning
confidence: 99%